Strategi Manajemen Media dalam Distribusi Konten di Era Penyiaran Digital: Studi Kasus pada TVMu - Aprianto, Adityo; Sanjaya, Makroen (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
In facing the digital era, there is a change in conventional broadcasting to digital broadcasting with a focus on multiplatform content distribution. This encourages TVMU to adapt to digital broadcasting. This study aims to understand how media, especially TVMU, formulates strategies, chooses the right approach, implements, and conducts monitoring and evaluation to increase the relevance and reach of its broadcasts. The Media Management Strategy Theory that became the focus of the research from Media Strategy Formulation, Media Strategy Selection, Media Strategy Implementation, Monitoring and Evaluation. A qualitative approach with a case study method was used to extract data through observation and in-depth interviews with relevant informants. The results show that multiplatform content distribution is the main strategy in facing the challenges of digital broadcasting. Social media is utilized for promotion, interaction, and distribution of program excerpts, while the website serves as an additional channel for live streaming and information provision. Television remains the main focus, but digital platforms are used to expand audience reach and attract the younger generation. Monitoring and evaluation processes are conducted regularly to assess the effectiveness of the strategies implemented, with adjustments based on analysis of audience data and digital trends. Key challenges include copyright issues on digital platforms and the difficulty of attracting audiences to educational and da'wah content amidst the dominance of entertainment content. The study concludes that implementing an integrated and adaptive content distribution strategy is an important step to support media sustainability in the digital era. The findings provide guidance for other media in effectively managing content distribution to reach a wider audience.